Assessment of Delivery Quality Assurance for Stereotactic Radiosurgery With Cyberknife - Li, Jun; Zhang, Xile; Pan, Yuxi; Zhuang, Hongqing; Wang, Junjie; Yang, Ruijie (Frontiers in Oncology, 2021)
Purpose: The purpose of this study is to establish and assess a practical delivery quality assurance method for stereotactic radiosurgery with Cyberknife by analyzing the geometric and dosimetric accuracies obtained using a PTW31016 PinPoint ionization chamber and EBT3 films. Moreover, exploring the relationship between parameters of plan complexity, volume of target and deliverability parameters to provide a valuable reference for improving plan optimization and validation Methods: 150 cases of delivery quality assurance plans were performed on Cyberknife for assessing point dose and planar dose distribution respectively using a PTW31016 PinPoint ionization chamber and Gafchromic EBT3 films. The measured chamber doses were compared with the planned mean doses in the sensitive volume of the chamber, and the measured planar doses were compared with the calculated dose distribution using gamma index analysis. The gamma passing rates were evaluated using criteria of 3% /1 mm and 2%/2 mm. The statistical significance of the correlations between the parameters of complexity metrics, target volume and the gamma passing rate were analyzed using Spearman’s rank correlation coefficient. Results: For point dose comparison, the averaged dose differences (± standard deviations) were 1.6±0.73% for all the cases. For planar dose distribution, the mean gamma passing rate for 3% /1 mm, and 2% /2 mm evaluation criteria were 94.26% ± 1.89%, and 93.86%±2.16%, respectively. The gamma passing rates were higher than 90% for all the delivery quality assurance plans with the criteria of 3%/1 mm and 2% /2 mm. The difference of point dose was low correlated with volume of PTV, number of beams and treatment time for 150 DQA plans, and high correlated with volume of PTV for 18 DQA plans of small target. DQA gamma passing rate (2%, 2 mm) was a moderate significant correlation for number of nodes, number of beams and treatment time, and a low correlation with MU. Conclusion: The point dose difference should be within 3%. The gamma passing rate should be higher than 90% for the criteria of 3%/1 mm and 2% /2 mm. In addition, the plan complexity and PTV volume were found to have some influence on the plan deliverability